Impact of family income in early life on the financial independence of young adults: Evidence from a matched panel data. (29th August 2019) - Cui, Xu; Xiao, Jing Jian; Yi, Jingtao; Porto, Nilton; Cai, Yi
Abstract: This study investigates whether the family income level in early life influences the financial independence of young adults. Using a large nationally representative U.S. sample (constructed based on the data from the 1999 to 2015 Panel Study of Income Dynamics, its 2009 to 2015 Transition to Adulthood Supplement and its 1997 to 2007 Child Development Supplement), we find that the relationship between one's family income level during adolescence and the financial independence of young adults follows an inverted U‐shape. We find that the college graduation status plays an important role in determining the financial independence of young adults. Once young adults graduate from the college, their financial independence is no longer influenced by their family income level during adolescence. The results show similar patterns after controlling for cognitive and noncognitive abilities and financial behaviours of young adults when they were children or teenagers. The findings of this study have significant implications for policymakers and educators.